Behavior-oriented inside network security situation modeling and analysis - Cheng ZHU; Jia-jia MIAO; Han-dong MAO (网络与信息安全学报)
According to the situation awareness theory as well as the characteristics of the inside network security,a PMDV model for behavior-oriented inside network security situation modeling by dividing the inside network space into physical domain,information domain and social domain was proposed.A sound base for situation modeling of inside network security,which classified the entities inside the network space into the following 4 classes:person(P),machine(M),data(D) and virtual agent(V),was provided and the core element “behavior” in situation model with the interactions between different PMDV entities was defined.The structure and implementation guideline of the situation analysis platform based on PMDV model were also presented and studied.